The Examining the Impact Islamic Religious Education and Ethics Learning on Student’ Ethical Behavior and Attitudes - Rusdi, Rusdi; Hafiz, Maulana (Faculty of Education and Teacher Training of UINSI Samarinda, 2023)
The problem of forming ethics and attitudes of students at SMK Negeri 8 Samarinda was formulated based on initial observations that students were found to be rude in speaking, did not pay attention to teachers, and skipped classes, presenting challenges for Islamic Religious Education and Ethics learning to be resolved. This research aims to measure the influence of Islamic Religious Education and Ethics learning on students’ ethics and attitudes. Quantitative type research with causal approach. The population in this research was 102 students of grade X OTKP SMKN 8 Samarinda. The sample size of 84 students was determined by the formula of Issac and Michael with a significance level of 5%. Data collection uses observation to determine initial conditions in the field, questionnaires to obtain data on variable X, variable Y1, and variable Y2, and documentation to obtain supporting data. Data analysis using correlation tests, coefficients of determination, and simple linear regression. The results obtained there were the positive influence of Islamic Religious Education and Ethics learning on student ethics and attitudes as evidenced by the results of the Pearson Correlation hypothesis test with a significance level of 0.000 < 0.05 with R square measurements indicating the magnitude of the correlation of variables X on Y1 by 22.9% and X on Y2 by 10%. Based on Simple Linear Regression Tests, every addition of Islamic Religious Education and Ethics learning by 1% could improve students’ ethics by 42.5% and students’ attitudes by 25.4%. Keywords: Islamic religious education, ethics, attitudes